Початковий етап розслідування вбивств, вчинених в умовах неочевидності - Жерж, Н. А.; Zherzh, N. (Одеса : Юрид. л-ра, 2014)
Article is devoted to practical and related theoretical issues investigation unobvious kills. The publication is aimed at the proper organization of the initial stage of investigation of crimes committed in conditions of non-obviousness.
Жерж Н. А. Початковий етап розслідування вбивств, вчинених в умовах неочевидності / Н. А. Жерж // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 406-412.
Keywords: злочин; неочевидне вбивство; початковий етап розслідування; методика розслідування; преступление; неочевидное убийство; начальный этап расследования; методика расследования; crime; unobvious murder; initial stage of the investigation; investigation procedure